Nose-Only Water-Pipe Smoke Exposure in Mice Elicits Renal Histopathological Alterations, Inflammation, Oxidative Stress, DNA Damage, and Apoptosis - Nemmar, Abderrahim; Beegam, Sumaya; Yuvaraju, Priya; Yasin, Javed; Ali, Badreldin H.; Adeghate, Ernest (Frontiers in Physiology, 2020)
The prevalence of water-pipe tobacco smoking is increasing worldwide, and is relatively high among youth and young adults. Exposure to water-pipe smoke (WPS) has been reported to affect various systems including the respiratory, cardiovascular and reproductive systems. However, the impact of WPS exposure on the kidney has received only scant attention. Here, we assessed the effect of nose-only WPS exposure for one or four consecutive weeks on renal histology, inflammation, oxidative stress, DNA damage and apoptosis. The duration of the session was 30 min/day and 5 days/week. Control mice were exposed to air. Light and electron microcopy analysis revealed that the WPS exposure (especially at four-week time point) caused degeneration of the endothelial cells of the glomerular capillaries and vacuolar degenerations of the proximal convoluted tubules. WPS exposure also significantly decreased the creatinine clearance, and significantly increased proteinuria and urinary kidney injury molecule-1 (KIM-1) concentration. Kidney lipid peroxidation, reactive oxygen species and oxidized glutathione were significantly increased. WPS exposure also affected the concentration of reduced glutathione and the activity of catalase. Likewise, renal concentrations of interleukin (IL)-6, IL-1β and KIM-1 were augmented by WPS exposure. Moreover, WPS caused DNA damage as evaluated by comet assay, and increased the expression of cleaved caspase-3 and cytochrome C in the kidney. We conclude that exposure of mice to WPS caused renal histopathological alterations, inflammation, oxidative stress, DNA damage and apoptosis. If the latter findings could be substantiated by controlled human studies, it would be an additional cause for disquiet about an established public health issue.